Revealing Public Service Quality: Assessing Satisfaction Levels and Performance in a Local Administrative Unit - Lestari, Arum Putri Damayanti; Sukmana, Hendra (Indonesian Journal of Public Policy Review, 2023)
This study delves into the pivotal role of service quality in organizational development, focusing on public service satisfaction at the Suko Village Office, Sidoarjo Sub-district, Sidoarjo Regency. Employing a descriptive quantitative approach through survey methodology, 390 respondents were randomly sampled. Data collection involved primary and secondary sources, while analysis utilized the Community Satisfaction Index (CSI) based on 9 service elements following the Indonesian Minister of Administrative and Bureaucratic Reform Regulation No. 14/2017. Results reveal an average score of 0.111 across the 9 service elements, with the perception interval indicating service quality and performance falling within the "Very Good" category (A). Notably, Service Element U7 (Service Behavior) attained the highest score with an interval value of 3.48 (A), while U9 (Facilities and Infrastructure) marked the lowest with a score of 3.30 (A). This underscores the need for continued focus on infrastructure improvements despite commendable service quality and performance across most domains. Highlights: Methodology: Utilized quantitative survey methodology with 390 randomly sampled respondents. Service Element Analysis: Revealed varying satisfaction levels across 9 service elements, highlighting high performance in Service Behavior and the need for improvement in Facilities and Infrastructure. Performance Assessment: Overall assessment indicated "Very Good" service quality and performance, signaling effective service delivery within the studied administrative unit. Keywords: Public Service Quality, Community Satisfaction, Service Performance, Survey Methodology, Service Elements